UTILIZATION RATE OF DENTAL SERVICES IN THE ERA OF NATIONAL HEALTH INSURANCE IN PRATAMA CLINIC, CITY OF JEPARA - Wardhana, Erdianto Setya; Yusuf, Mohammad; Salwa, Maila Samicha (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: The utilization rate is the use of dental and oral health which can be calculated using the number of National Healthcare Security (BPJS) patients per month compared to the number of BPJS participants multiplied by 100%Method: This study was an observational study used cross sectiona design and nominal data scale that produced quantitative data which was carried out by analysing the Pcare data started from March-August 2019 in eight primary clinics of Jepara City and District. Before conducted the study, Ethics Review No.098 / b.1-KEPK / SA-FKG / VII / 2019 was done.Result: The results of the utilization rate study based on the visit rates, Armina Pratama Clinic was 1.585%, Multisari II Pratama Clinic was 0.665%, Sentra Husada Pratama Clinic was 0.68%, Jepara General Pratama Clinic was 2.329%, Yasmin Medika Pratama Clinic was 2.173%, Hanis Pratama Clinic was 0.752%, Az-Zahra pratama clinic 2.945%, and Armina Denta pratama clinic was 1.885%.Conclusion: In conclusion, the utilization rate based on pratama clinic visits in the city and the regency of Jepara was still in the low to the ideal category. Meanwhile, the utilization rate based on the referral numbers of pratama clinic in the city and the regency of Jepara was far from the standard value